QOLP-27. USE OF THE NEURO-QOL COGNITIVE FUNCTION SHORT-FORM AS A TOOL FOR ASSESSING PATIENT-PERCEIVED NEUROCOGNITION FOLLOWING RADIOTHERAPY. (9th November 2020) - Choi, Sung; Kowalski, Emily; Khairnar, Rahul; Mishra, Mark
Abstract: The Quality-of-Life in Neurological Disorders (Neuro-QOL) instruments are a practical set of validated tools utilized to measure a core set of health-related quality-of-life parameters that are relevant to patients with neurological disorders. The tools can be completed in approximately 1-minute. The primary objective of this study was to evaluate the feasibility of utilizing the eight-question Neuro-QoL Cognitive Function- Short Form (NCF-SF) tool (v2.0) to assess cognitive outcomes in patients with primary and secondary brain tumors undergoing radiotherapy. Patients completed the NCF-SF at baseline and during follow-up visits. Raw scores were converted to a standardized T-score that has been normalized to have mean score of 50 and standard deviation (SD) of 10. Descriptive statistical analyses were performed to assess the prevalence of baseline cognitive impairment (defined as > 1 SD below the normative mean), and to assess longitudinal changes in Neuro-QOL scores. A minimum clinically important difference (MCID) was defined as a change from baseline of >7.5, based on previously published literature. Ninety-one patients completed NCF-SF at baseline and at least one follow-up visit. The mean baseline score for the study cohort was 49.9 (SD 9.2). Nineteen percent of patients (n=17/91) had impaired function at baseline. Baseline scores did not differ based on tumor type (p=0.79): Glioma/ependymoma 49.6 (n=35); brain metastases 49.1 (n=24); Meningioma/benign 50.7 (n=32). Following radiation, 15% and 22% of patients experienced a MCID decline at 1- (n=60) and 3- months (n=65), respectively. However, 17% and 20% of patients demonstrated a MCID improvement at 1- and 3-months, respectively. In conclusion, this represents the first study to utilize the NCF-SF to measure cognitive function in patients undergoing brain radiotherapy. Use of NCG-SF was feasible, and identified patients with meaningful changes in cognitive function over time. Future clinical trials may consider use of Neuro-QOL to assess patient-perceived cognitive function.